2022
DOI: 10.15252/embr.202254736
|View full text |Cite
|
Sign up to set email alerts
|

The plant‐specific DDR factor SOG1 increases chromatin mobility in response to DNA damage

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 63 publications
(85 reference statements)
0
18
1
Order By: Relevance
“…Recently, a report on the lncRNA COOLAIR involved in the regulation of flowering time revealed that environmental conditions resulted in alternative processing and variability in secondary structures (Yang et al, 2022). In connection with DNA repair, there is growing evidence that this involves large scale reorganization of the chromatin, e.g., by changing chromatin mobility (Meschichi et al, 2022; Meschichi and Rosa, 2023) or the formation of foci with assembly of repair factors (Hirakawa et al, 2015; Hirakawa and Matsunaga, 2019; Muñoz-Díaz and Sáez-Vásquez, 2022). It remains to be investigated whether and how lncRNAs are involved in this compartmentalization, but the candidates identified in the course of the work presented and the improved techniques to visualize RNA molecules within cells (Duncan and Rosa, 2018; Huang et al, 2020) will make these approaches possible.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a report on the lncRNA COOLAIR involved in the regulation of flowering time revealed that environmental conditions resulted in alternative processing and variability in secondary structures (Yang et al, 2022). In connection with DNA repair, there is growing evidence that this involves large scale reorganization of the chromatin, e.g., by changing chromatin mobility (Meschichi et al, 2022; Meschichi and Rosa, 2023) or the formation of foci with assembly of repair factors (Hirakawa et al, 2015; Hirakawa and Matsunaga, 2019; Muñoz-Díaz and Sáez-Vásquez, 2022). It remains to be investigated whether and how lncRNAs are involved in this compartmentalization, but the candidates identified in the course of the work presented and the improved techniques to visualize RNA molecules within cells (Duncan and Rosa, 2018; Huang et al, 2020) will make these approaches possible.…”
Section: Discussionmentioning
confidence: 99%
“…In both yeast and animals, chromatin mobility is restricted by proximity to tethering structures such as the nuclear envelope and centromeres (Chubb et al, 2002;Hajjoul et al, 2013;Heun et al, 2001;Verdaasdonk et al, 2013). In Arabidopsis, lacO/lacI lines with lacO sequences inserted in different chromosomal positions displayed different mobilities (Matzke et al, 2008(Matzke et al, , 2010Meschichi et al, 2022). Lines with insertions corresponding to nucleoplasmic regions showed similar levels of chromatin mobility, whereas a locus with subtelomeric localization showed a significant reduction in mobility compared to the other lines.…”
Section: Factors That Influence Chromatin Mobilitymentioning
confidence: 99%
“…Lines with insertions corresponding to nucleoplasmic regions showed similar levels of chromatin mobility, whereas a locus with subtelomeric localization showed a significant reduction in mobility compared to the other lines. (Meschichi et al, , 2022.…”
Section: Factors That Influence Chromatin Mobilitymentioning
confidence: 99%
See 2 more Smart Citations